Pengaruh Fasilitas, Motivasi, dan Kedisiplinan Terhadap Prestasi Belajar MIPA di SMA Negeri 1 Ceper Kabupaten Klaten - Synder Prasetyo (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2020)
The objectives to be achieved in this study are to find out the influence oflearning facilities at home on the learning achievement, effect of learning motivation,effect of learning discipline, learning achievement of Mathematics and NaturalSciences in Class XI MIPA students of SMA Negeri 1 Ceper, Klaten Regency. Theresults showed, (1) Effective contribution or the influence of learning facilities athome, MIPA learning motivation and learning discipline towards MIPA learningachievement 63.5% and the remaining 36.5% influenced by other variables notincluded in the this research. (2) The effective contribution of learning facilities athome to the learning achievement of Mathematics and Natural Sciences students was12.2% and the relative contribution was 19.2%. (3) The effective contribution ofMIPA learning motivation towards the learning achievement was 38.8% and therelative contribution was 61.1%. (4) The effective contribution of learning disciplineto the learning achievement of Mathematics and Natural Sciences students was 12.5%and the relative contribution was 19.7%. (5) MIPA learning motivation is anindependent variable that has the greatest influence on the learning achievementwhile learning facilities at home have the least influence on MIPA learningachievement.